Extrapulmonary manifestations of COVID-19 patient presenting with abdominal pain and skin lesions as primary symptoms - Kumar, Abhishek; Prasad, Dinesh; Gahlot, Vishnu (International Surgery Journal, 2021)
COVID-19 is basically a respiratory disease and pulmonary manifestations constitute main presentations of the disease however in some patients SARS-CoV-2 infection is not limited to the respiratory system and other organs can also be affected and may be the primary manifestations of the disease.Renal dysfunction, gastrointestinal complications, liver dysfunction, cardiac manifestations, neurological abnormalities, haematological and thrombotic manifestations are among the reported extrapulmonary features. Given that ACE2, the entry receptor for the causative coronavirus SARS-CoV-2, is expressed in multiple extrapulmonary tissues, direct viral tissue damage is a plausible mechanism of injury. In addition, endothelial damage and thrombo-inflammation, dysregulation of immune responses, and maladaptation of ACE2-related pathways might all contribute to these extrapulmonary manifestations of COVID-19. Considering the broad spectrum of clinical manifestations and the increasing worldwide burden of the disease, there is an urgent need to evaluate patients presenting with abdominal symptoms and skin lesions even without respiratory complaints to increase the diagnostic accuracy to detect COVID-19 and its complications in early stage. Our case report documents a patient who presented with abdominal symptoms and skin lesions whose RT-PCR was positive for COVID-19. It remains to be seen whether these patients will eventually develop respiratory symptoms. Further studies are needed to elaborate and confirm the causative relationship between SARS-CoV-2 and the reported extrapulmonary manifestations of COVID-19.